Investigation of pH varied anthocyanin pigment profiles of Agapanthus praecox and its potential as natural colourant - Yaacob, J.S.; Yussof, A.I.M.; Abdullah, S.; Ramesh, K.; Taha, R.M. (2011)
Anthocyanin pigment profiles, colours and pH values of Agapanthus praecox were investigated. The anthocyanin pigments from the blue flower petals were solvent extracted with 70 acetone, and the pH of the extracts was varied (pH 1, 2.5, 4.5 and 7). The colour of the pigment solution changed with pH, where it became pinkish purple at pH 1, dark red at pH 2.5, light purple at pH 4.5, dark turquoise at pH 7, dark green at pH 9.5, light green at pH 11.5 and yellow at pH 14. The extracts were also subjected to ultraviolet-visible spectrophotometric analysis, where a distinct peak at 544 nm was observed for both pH 1 and 2.5, while multiple peaks at 535, 571.5 and 627 nm were observed for pH 4.5 and at 535, 574 and 620 nm for pH 7. The anthocyanin extract with the most stable pH (at pH 1) was mixed with 20 poly(methyl methacrylate) and coated onto glass slides, which was then subjected to weathering tests to determine its durability.